The impact of state paid leave laws on firms and establishments: Evidence from the first three states - Kristin F. Butcher; Deniz Civril; Sari Pekkala Kerr (Federal Reserve Bank of Chicago, 2024)
We use the Longitudinal Business Database to examine the impact of state-level paid parental leave laws in California, New Jersey, and Rhode Island on firms. Our main estimation strategy uses multi-unit firms and compares within-firm changes in outcomes for establishments in treated and untreated states. We find that paid parental leave laws reduce employment in firms' establishments in treated states. We investigate heterogeneity of the effects by pre-mandate share of workers in an industry that were women, and find that there is no systematic evidence that firms reduce employment more in industries with a higher share of women employees.
Keywords: H75; J13; J18; J21; J23; J31; J63; 330; Paid leave; employment; firms; establishments; entry; exit; revenue; productivity